Increase customer loyalty by customer bonding and customer relationship management - Dyah Ika Kirana Jalantina; Maria Magdalena Minarsih (Institute of Computer Science (IOCS), 2023)
This look at goals to analyze the impact of patron bonding and patron courting management on customer loyalty via consumer delight on Lifebuoy brand soap products. Today's an increasing number of fierce sales opposition can be expected by using Unilever as a producer of Lifebuoy tub cleaning soap via enforcing consumer relationship control as a way to win the competition. The company also applies client bonding as a shape of bonding between customers and the company. This studies is a quantitative studies the use of number one facts. Using a couple of regression analysis method, records collection by way of the use of a questionnaire. Samples have been taken as many as a hundred respondents with an age extra than or identical to 17 years and are customers of Lifebuoy soap. The results confirmed that Customer Bonding (X1) has a positive and enormous impact on Customer Satisfaction (Z), Customer Relationship Marketing (X2) has a fantastic and large impact on Customer Satisfaction (Z), Customer Satisfaction (Z) has a high-quality and full-size effect on Customer loyalty (Y), Customer Satisfaction (Z) is able to mediate the connection between Customer Bonding (X1) and Customer Loyalty variables, Customer Satisfaction (Z) is able to mediate the connection between Customer Relationship Marketing (X2) variables and Customer Loyalty.